(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, an understanding of the modern methods of ecotourism development in Uzbekistan, prospects for the development of ecotourism and the goal of ecotourism development is given. Also, the article examines the concept and types of ecotourism and reveals their interrelationships.